MANAJEMEN KONFLIK KONSERVASI BANTENG (Bos javanicus D'ALTON 1823) DI KAWASAN TAMAN NASIONAL MERU BETIRI DAN TAMAN NASIONAL ALAS PURWO - R Garsetiasih; Hadi S Alikodra (Jurnal Analisis Kebijakan Kehutanan, 2015)
Study on conflict management of bulls (Bos javanicus d'Alton 1823) conservation and community in Meru Betiri National Park (MBNP) and Alas Purwo National Park (APNP) East Java were conducted on December 2009 to December 2011. The aims of study was to identify stakeholder who have conflict with bulls conservation. The main aim of the study to formulate conservation of bulls by using collaborative management as a solution management of bulls conflict. The methods of study were using stakeholder grid, hierarchy process (AHP) and SWOT analysis. The result showed that the main stakeholders who have interested on bulls management in Meru Betiri National Park (MBNP) and Alas Purwo National Park (APNP) were plantation company, Perum Perhutani, community around national park, NGO KAIL and national park management. The model of bulls conflict management solution was co-management by develop programe, and activity of conflict management type through habitat management (instructive), captive breeding (cooperative), ecotourism (advocacy) and development of medicine and fruits tree (cooperative).